Some migration aspects, trends and issues in the North and Central Asia: case of Kazakhstan (International relations and international law Journal, 2018)
Migration and mobility in the post-Soviet space are part of the global process for more than a quarterof a century. Possessing almost all the main characteristics of the global process, migrations in thisspace have their own characteristics and specifics that require special attention and understanding. Toanalyze the mobility of this space, the definitions and approaches that determine the potential systemsand subsystems that cover this process are important. Kazakhstan is one of the states in this space forwhich migration issues and demographic development are a strategic direction, including within theframework of the Eurasian Economic Union. An important issue remains the choice of the approach thatdefines the given space not only geographically, but also geo-economically, and geo-politically. One ofthe effective in this approach can be the use of the UN definition of “North and Central Asia”, coveringthe main participants of the migration process. The main purpose of this article is a review of some ofthe main national and regional aspects of the migration processes in the Republic of Kazakhstan at thepresent stage. Since the beginning of the 21st century, Kazakhstan has positioned itself as a host countryfor migrants, being simultaneously a major transit corridor. Recently there has been a tendency of an activeoutflow of the population, which is a definite challenge that requires due attention and evaluation.The methodological basis of the study is a systematic approach that allows a comprehensive assessmentof migration processes, as well as the theory of “pull-push factors.” This study may be important in thecontext of the analysis of common Central Asian processes of cooperation and integration, and from thepoint of view of developing a theoretical component of the migration processes.Key words: International Relations, Migration, Kazakhstan, Labor Migration, Eurasian EconomicUnion.